دور السلم في تمويل الاستثمار )النشاط الزراعي -انموذجا - سلامي, أسامة; سماري, جيهاد; قتال, خولة (University of Eloued-جامعة الوادي, 2016)
يعتبر عقد السمم أحد البيوع التي رخص فييا لحاجة الناس إلييا، وقد شيد مؤخ ا رً عدة تطبيقات معاصرة في مجال الاستثمار وذلك لما لو من دور كبير في العمل التمويمي، وكان ىذا الموضوع محل بحثنا وقد اعتمدنا في د ا رستو عمى الخطة التالية: حيث قسمناه إلى مبحثين، تناولنا في المبحث الأول الإطار النظري)السمم، التمويل، الاستثمار( ويندرج تحتو ثلاثة مطالب، وأما المبحث الثاني فبعنوان نماذج من تطبيق عقد السمم في البنوك الإسلامية لتمويل النشاط الز ا رعي والمعوقات والمخاطر التي تواجيو، ويحتوي عمى ثلاث مطالب. وفي النياية توصمنا إلى أن عقد السمم أداة ناجحة في الحد من بعض المعاملات الربوية في التمويل. ABSTRACT: Essalam contract is considered one of the sellings types that are authorized because of people needs. This contract have seen later many modern aplications in the investissement domain because of its importance roleregarding the financial operation. This subject is the main of our project, and in our study we have put the following plan: firstly, we divided the project into two parts, the first part is the theoretical side as:) Essalm...Financé...Investissement(. Under this part we put three divisions. In the second part is titled as: models offinance and the obstacles and risks that face it, under this part there are three divisions. In the finally, as a conclusion Essalam contract is a successful way To limit some of unfair financial operations. Essalam contract aplications in Islamic banks for agriculture activity
مذكرة ليسانس
Keywords: السلم /الاستثمار/النشاط الزراعي; Paix/investissement/activité agricole